Habituation and Experiential Learning (HaEL) Methods for Improving HOTS Skills through Active Learning: A Path Toward the SDGs in Islamic Education - Muhammad Arifin Rahmanto; Waston; Sekar Ayu Aryani; Bunyamin (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to examine how the Habituation and Experiential Learning (HaEL) method enhances Higher-Order Thinking Skills (HOTS) through active learning and contributes to the achievement of the Sustainable Development Goals (SDGs) in Islamic education. Theoretical framework: The study is grounded in the theoretical framework of experiential learning, habituation theory, constructivist learning, and Higher-Order Thinking Skills, which collectively emphasize the development of critical, analytical, creative, and reflective competencies through continuous practice and meaningful learning experiences. Literature review: Previous studies have demonstrated the effectiveness of active learning and experiential approaches in improving students’ cognitive achievement; however, limited research has integrated habituation and experiential learning into a unified pedagogical model while explicitly linking HOTS development with the SDGs in Islamic education. Method: Employing a descriptive qualitative design, this research involved 15 informants comprising the vice principal, Islamic Education teacher, and Grade X and XI students from the Office Management and Animation programs at SMKN 3 Tangerang Selatan. Results: The findings reveal three major challenges affecting HOTS development, namely students’ limited critical thinking habits, insufficient implementation of active learning strategies, and the lack of systematic integration of SDGs values into Islamic Education instruction. The HaEL method addresses these challenges by combining structured habituation with experiential learning activities that encourage collaboration, problem-solving, reflection, and authentic classroom engagement. Implications: The study implies that integrating HaEL into Islamic education can strengthen educational quality, foster lifelong learning competencies, and support schools in implementing SDG 4 through innovative pedagogy. Novelty: The novelty of this research lies in proposing HaEL as an integrated pedagogical framework that combines habituation and experiential learning to systematically cultivate HOTS while embedding SDGs-oriented values into Islamic education.